ROLE OF PARENTS IN EXCESSIVE SCREEN TIME AND IT’S EFFECT ON CHILDREN: A SYSTEMATIC REVIEW (International Journal of Food and Nutritional Sciences, 2022)
According to World Health Organization (WHO) guidelines, Children under 2 years of age should not have any screen exposure, and children between two and four years of age should not have more than 1 hour of screen time at a time. They should not spend too much time staring at a screen. Children who watch mobile, TV, or other screens for too long can hurt their physical, emotional, and mental health. A lack of exercise and excessive screen use is linked to obesity, headaches, back discomfort, vision difficulties, and sleep deprivation. The main goal of this systematic study is to explore the relationships between parental involvement, screen use, and their influence on children's dietary behaviors and other related areas. The findings suggest that many children exceed the recommended television viewing duration, often due to uneven parental supervision. Compared to kids whose screen usage was consistently monitored, kids whose screen usage was inconsistently monitored were considerably more likely to have suspected attention, cognitive, and social skills deficiencies. However, supervised screen viewing did not differ significantly by gender. This study underscores the importance of understanding and addressing these patterns to promote healthier habits, better nutritional choices, and more balanced screen use among children by the parents. The study gap highlights the lack of knowledge on the benefits and disadvantages of time spent on screens for kids. It also raises questions about parental modeling, the impact of parenting methods on-screen usage, and the relationship between parents' anxiety and stress levels. Further research is needed to understand how parents manage screen usage, the impact of parental stress on screen time guidelines, and the effectiveness of online resources for limiting screen usage.